INNOVATIVE FOOTWEAR DESIGN FOR AUTISTIC INDIVIDUALS: MERGING AESTHETICS AND SENSORY NEEDS (International Seven Journal of Multidisciplinary, 2024)
The integration of repetitive visual patterns and geometric shapes in footwear design for autistic individuals presents an innovative approach that transcends mere aesthetics. This strategy aims to address the sensory and emotional needs of users, highlighting the importance of visual stimuli in promoting focus and mental organization—key elements for those facing sensory challenges. Research indicates that emphasizing symmetry and repetition in design can create visually pleasing footwear while also facilitating better concentration. Various studies suggest that the perceptual abilities and visual processing strategies of autistic individuals can be harnessed to foster richer and more effective learning experiences, aiding in the development of essential social and cognitive skills. Furthermore, the selection of comfortable materials and the consideration of ergonomic design are crucial to ensure that the shoes are not only visually appealing but also functional and comfortable for everyday wear. By focusing on these aspects, footwear can serve as more than just a fashion statement; it can become a tool for enhancing the quality of life for autistic individuals. The thoughtful combination of art, comfort, and sensory experience in shoe design promotes inclusion and celebrates the uniqueness of each individual. This approach fosters a deep connection between the user and the product, ultimately contributing to a more supportive and understanding environment for those on the autism spectrum.